2009
DOI: 10.1093/nar/gkn798
|View full text |Cite
|
Sign up to set email alerts
|

VarySysDB: a human genetic polymorphism database based on all H-InvDB transcripts

Abstract: Creation of a vast variety of proteins is accomplished by genetic variation and a variety of alternative splicing transcripts. Currently, however, the abundant available data on genetic variation and the transcriptome are stored independently and in a dispersed fashion. In order to provide a research resource regarding the effects of human genetic polymorphism on various transcripts, we developed VarySysDB, a genetic polymorphism database based on 187 156 extensively annotated matured mRNA transcripts from 36 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 20 publications
(13 reference statements)
0
17
0
Order By: Relevance
“…However, it advances the possibility for a stronger predictability of non-harmful variations, which is helpful for defining thousands of unclear changes under the current knowledge and databases. For example, in VarySysDB , the database recently developed by Shimada et al (2009), the next changes remain unclear, while by using the rules of variation reported here, we may conclude that in general, these variations were non-harmful: (1) Agrin (AGRN): Gtc / Atc bringing a Val/Ile change (Rule 1), (2) protein kinase C zeta (PRKCZ): ttC / ttG causing a Phe/Leu replacement (Rule 1), (3) Von Willebrand factor A domain-related protein isoform 1: gCg / gTg changing Ala/Val (Rule 3), (4) multiple epidermal growth factor-like domain 6 precursor (MEGF6): gCg / gTg causing Ala/Val change (Rule 3), and (5) stromal cell-derived factor 4 (SDF-4): Cag / Gag changing Gln/Glu (Rule 2).…”
Section: Discussionmentioning
confidence: 99%
“…However, it advances the possibility for a stronger predictability of non-harmful variations, which is helpful for defining thousands of unclear changes under the current knowledge and databases. For example, in VarySysDB , the database recently developed by Shimada et al (2009), the next changes remain unclear, while by using the rules of variation reported here, we may conclude that in general, these variations were non-harmful: (1) Agrin (AGRN): Gtc / Atc bringing a Val/Ile change (Rule 1), (2) protein kinase C zeta (PRKCZ): ttC / ttG causing a Phe/Leu replacement (Rule 1), (3) Von Willebrand factor A domain-related protein isoform 1: gCg / gTg changing Ala/Val (Rule 3), (4) multiple epidermal growth factor-like domain 6 precursor (MEGF6): gCg / gTg causing Ala/Val change (Rule 3), and (5) stromal cell-derived factor 4 (SDF-4): Cag / Gag changing Gln/Glu (Rule 2).…”
Section: Discussionmentioning
confidence: 99%
“…Transcription may also be modified by copy number variations (CNV), insertions and deletions, short tandem repeats and single amino acid repeats 23 . A systematic investigation of the effects of CNVs in individuals who are part of the International HapMap project showed that SNPs and CNVs captured 84% and 18% of the total detected genetic variation in gene expression, respectively, but the signals from the two types of variation had little overlap.…”
Section: Eqtl Mappingmentioning
confidence: 99%
“…VarySysDB offers information encompassing published human genetic polymorphisms for each of these transcripts separately. In addition to SNP effects on transcription, this database includes deletion-insertion polymorphisms from dbSNP (http://www.ncbi.nlm.nih.gov/projects/SNP/), copy number variations from Database of Genomic Variants (http://projects.tcag.ca/variation/), short tandem repeats and single amino acid repeats from H-InvDB (http://www.h-invitational.jp/) and linkage disequilibrium regions from D-HaploDB (http://orca.gen.kyushu-u.ac.jp/) 23 .…”
Section: Eqtl and Disease-gene Mappingmentioning
confidence: 99%
“…Other tools with a similar scope that were recently developed as, for example, SNPnexus [14] or VarySysDB [15] harness a variety of external data sources to characterize polymorphisms, but are based on static datasets restricted to human and offer only limited batch processing capabilities.…”
Section: Introductionmentioning
confidence: 99%